1990
DOI: 10.1002/vnl.730120110
|View full text |Cite
|
Sign up to set email alerts
|

Use of regrind in the PVC extrusion process

Abstract: Extrusion products that to not meet specification are generally reground for extrusion reprocessing. This paper describes the effect of heat history of regrind materials on extrusion quality, including surface appearance (melt fracture), toughness, edge tear, and heat stability. It is hoped that the information presented in this paper will help processors optimize use of regrind for best performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…They also reported that the maximum amount of recyclate that can be added to virgin PVC bottle and PVC pipe grades, to achieve the optimum ultimate tensile strength (UTS), is 40 and 80 wt%, respectively. Rabinovitch et al reported that, in order to achieve a smooth surface in a PVC regrind‐incorporated sample, the melt temperature of the secondary extrusion must be at least 8–10°C higher than its previous heat history. Ditta et al investigated the recyclability of postconsumer U‐PVC window profiles over several repeated extrusion cycles.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that the maximum amount of recyclate that can be added to virgin PVC bottle and PVC pipe grades, to achieve the optimum ultimate tensile strength (UTS), is 40 and 80 wt%, respectively. Rabinovitch et al reported that, in order to achieve a smooth surface in a PVC regrind‐incorporated sample, the melt temperature of the secondary extrusion must be at least 8–10°C higher than its previous heat history. Ditta et al investigated the recyclability of postconsumer U‐PVC window profiles over several repeated extrusion cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Recycling processes vary in terms of quality of recyclate, cost, complexity, and environmental impact. Size reduction processes [4] such as granulation, shredding, pulverizing, and micronizing convert waste products into a form which can be reprocessed, if necessary after ferrous metal removal by magnets. This is a simple recovery process suitable for products where the purity of the source waste is high (e.g., pre-use window profile or supermarket collation trays) or where the contaminants can be readily separated (e.g., cable sheathing and copper core).…”
Section: Introductionmentioning
confidence: 99%